Decompositions of Complete Multigraphs into Cyclic Designs - Mowafaq Alqadri; Haslinda Ibrahim; Sharmila Karim (JOIV : International Journal on Informatics Visualization, 2020)
Let  and  be positive integer,  denote a complete multigraph. A decomposition of a graph  is a set of subgraphs of  whose edge sets partition the edge set of . The aim of this paper, is to decompose a complete multigraph  into cyclic -cycle system according to specified conditions. As the main consequence, construction of decomposition of  into cyclic Hamiltonian wheel system, where , is also given. The difference set method is used to construct the desired designs.